Effectiveness of a Work Safety Culture and Health Education Module in improving office-related ergonomics of public sector administrative workers in Abeokuta, Nigeria - Odu, Josiah Oluwaseun (2022)
Studies have shown that a workplace safety culture (WSC) is lacking among the general workforce in Nigeria. Poor WSC can result in adverse impacts on workers' health and high remedial costs for employers. To improve WSC, workers need to improve on knowledge, attitude, and practices related to office ergonomics towards WSC through effective health interventional programs at the workplace. The study aimed to develop, implement and evaluate the effectiveness of the Work Safety Culture Health Education Module (WSCHEM) among government administrative workers in Abeokuta, Southwestern Nigeria. The study was a two-armed, single-blinded cluster randomized controlled trial involving 247 public sector administrative workers from clusters of 20 ministries in Abeokuta, Southwestern Nigeria. The intervention group was given WSCHEM, whereas the waitlist group received a seminar on team building and leadership skills and received the WSCHEM after the intervention program ended. The researcher administered the module to the intervention group. For the waitlist group, one of the research assistants from the ministry of finance delivered the seminar on team building and leadership skills for morning and afternoon sessions. The evaluation was done three times using the first formal validated, self-administered Work Safety Culture Questionnaire (WSCQ) among the administrative workers: first at baseline, second at one month, and third at three months post-intervention. The validation of the Work Safety Culture Questionnaire (WSCQ) confirmed high reliability and validity for the evaluation of the level of knowledge, attitude, and practices toward work safety culture (WSC) among the study population. The respondents’ knowledge, attitude, and practices toward workplace safety culture (WSC) was measured using the Work Safety Culture Questionnaire (WSCQ). Data obtained was analyzed by using the IBM SPSS Statistics 25. Chi-Square Test was used for bivariate analysis, and Generalized Estimating Equations (GEE) for the multivariate analysis. The results showed no statistically significant differences between groups regarding the respondents’ characteristics (socio-demographic and occupational/office related ergonomic factors) and the outcome variables (knowledge attitudes and practices) on WSC at baseline. For practices towards WSC, both intervention (β 6.8, 95%CI 4.85, 8.72) and time (β 6.2, 95%CI 4.49, 7.94) had a statistically significant effect on the respondents’ practices towards WSC in the per-protocol analysis. In the secondary outcomes, both knowledge of WSC, intervention (β 3.5, 95%CI 2.8, 4.2) and time (β 3.4, 95%CI 2.7, 5.9) and attitudes towards WSC, intervention (β1.7, 95%CI 1.25, 2.23) and time (β 2.3, 95%CI 1.92, 2.76) had a significant effect on the respondents’ level of knowledge and attitudes respectively towards WSC. The WSCHEM effectively improved respondents’ knowledge, attitude, and practices related to office ergonomics (which are exercising, using computer screen cover, not sitting in one position for a long time, and attending office ergonomic course) toward work safety culture. Employers are encouraged to adopt WSCHEM as an adjunct to their workplace’s pre-existing control measures to improve their workers' knowledge, attitude, and practices toward work safety culture.